FUNDAMENTALISM AND RADICALISM IN ISLAM: AN EPISTEMOLOGICAL APPROACH - Muhammad, Rasyidin; Rijal, Syamsul (ILMU USHULUDDIN, 2021)
This paper attempts to examine how fundamental-radical epistemology forms after the return of the power of Taliban in Afghanistan. To arrive at this topic, the author would firstly review the terminology and historical roots of fundamentalism-radicalism, and the factors that caused its emergence and its characteristics. The author uses a historical-phenomenological approach in doing the literature research to write this article. In analyzing obtained data, the author is using descriptive-analytical, historical, and holistic techniques. The results found are: first, the emergence of the understanding of fundamental-radical, which was initially only a political phenomenon, turned out to lead to systemic violence, actual violence, action, and symbolic violence. These are still threatening humanity because of the characteristics of their movements that are unwilling to communicate and attempt dialogue with relevant groups. Second, the factors behind the rise of radicalism are two, namely: socio-political factors and religious-related emotional factors. Third, the epistemology of fundamental-radicals lays only on literal and textual understanding. According to them, the truth lies in the understood sacred text, as it is.